Peningkatan Keterampilan Membaca Pemahaman Dengan Metode Sustained Silent Reading Di Kelas IV UPT SPF SD Inpres Kelapa Tiga 1 Makassar - Fakhirah Amalia Lukman; Tarman A. Arif; Anin Asnidar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Fakhirah Amalia Lukman. 2023. Improving Reading Comprehension Skills using the Sustained Silent Reading Method in Class IV UPT SPF SD Inpres Kelapa Tiga 1 Makassar. Thesis. Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. This research aims to improve reading comprehension skills using the Sustained Silent Reading (SSR) method for class IV UPT SPF students at SD Inpres Kelapa Tiga 1 Makassar. The subjects used in this research were 23 students. This research procedure consists of 4 stages each cycle, namely planning, implementing actions, observing and reflecting. The indicator of reading comprehension in this research is the achievement of learning completeness. The data collection is an observation sheet and the final test of each cycle. The results of this research show that there is an increase in students' reading comprehension, namely in the first cycle of students' reading comprehension, an average score of 56.1 was obtained with a learning completeness of 26%. In cycle II the average score was 80.8 with learning completeness of 86.9%. Thus, it can be concluded that the application of the Sustained Silent Reading (SSR) method can improve reading comprehension in class IV students at UPT SPF SD Inpres Kelapa Tiga 1 Makassar.